Pengaruh Latihan Passing Sepakbola Push and Run dan Ball Feeling Terhadap Hasil Passing Sepakbola Klub Formal FC - Risko Renal Herlambang; Soemardiawan Soemardiawan; Ismail Marzuki (Jurnal Porkes, 2026)
The problem addressed in this study is that passing drills at Formal FC remain monotonous and poorly executed, resulting in low passing accuracy among players. The purpose of this study is to determine the effect of push-and-run and ball-feeling drills on the passing performance of Formal FC in 2026. The study employed an experimental method using a two-group pretest-posttest design. The sample consisted of 22 players divided into two groups: the push-and-run group with 11 players and the ball-feeling group with 11 players. The research instrument used the modified Vernon A. Crew passing-stopping test. The results showed that the push-and-run training increased the average score from 7.27 to 9.00 (increase of 1.73), while the ball-feeling training increased it from 7.36 to 9.27 (increase of 1.91). The paired t-test yielded a significance value of 0.001 for both groups, indicating a significant effect. The independent sample t-test on gain scores showed a significance value of 0.499, indicating no significant difference between the two training methods. In conclusion, both push-and-run and ball-feeling training significantly influence the improvement in passing accuracy among Formal FC players; however, there is no significant difference in the effects between the two training methods. Coaches are advised to use ball-feeling for players with low ball control and push-and-run to improve movement without the ball.